TikTok local wisdom: Building criticality in teaching Indonesian speaking skill for intermediate foreign speakers - Widia, Ida; Ulhaq, Nada Dhiya; Krisanjaya, Krisanjaya; Sundusiah, Suci; Kojima, Nao (Universitas Muhammadiyah Malang, 2026)
This study was motivated by the low level of integration of critical thinking skills in the teaching of Indonesian language speaking skills for foreign learners (BIPA) at the intermediate level, particularly in the context of utilizing digital media based on local wisdom. The main issue lies in the tendency for speaking instruction to still focus on linguistic fluency, without fully developing reflective argumentation and intercultural sensitivity. This study aims to explore and test the functional relationship between critical thinking skills and the speaking skills of intermediate-level BIPA learners through the use of TikTok content containing local wisdom. The method used was a quantitative approach with a Single Subject Research (ABA) design. Data were collected through speaking skill tests, classroom observations, in-depth interviews, and documentation of learning recordings among intermediate-level BIPA learners. Analysis was conducted visually and comparatively between the baseline and intervention phases to identify changes in speaking performance. The results showed an increase in speaking skill scores from the A1 baseline to the intervention phase (AN: 65.83 to 84.58; JN: 61.67 to 75) with an overlap percentage of 0%–16.67%, as well as performance stabilization at the A2 baseline (AN: 93.92; JN: 84.08) with an overlap of 0%–33.33%, while qualitative findings reinforced the transformation of systematic argumentation skills, cross-cultural evaluation, and critical reflection. Thus, the integration of critical thinking through TikTok infused with local wisdom has a positive functional relationship with the strengthening of speaking skills, making it an innovative alternative in BIPA speaking instruction that prioritizes reflective and intercultural thinking competencies.